Are sympatrically speciating Midas cichlid fish special? Patterns of morphological and genetic variation in the closely related species Archocentrus centrarchus. Issue 12 (20th May 2016) - Fruciano, Carmelo; Franchini, Paolo; Raffini, Francesca; Fan, Shaohua; Meyer, Axel
Abstract: Established empirical cases of sympatric speciation are scarce, although there is an increasing consensus that sympatric speciation might be more common than previously thought. Midas cichlid fish are one of the few substantiated cases of sympatric speciation, and they formed repeated radiations in crater lakes. In contrast, in the same environment, such radiation patterns have not been observed in other species of cichlids and other families of fish. We analyze morphological and genetic variation in a cichlid species ( Archocentrus centrarchus ) that co‐inhabits several crater lakes with the Midas species complex. In particular, we analyze variation in body and pharyngeal jaw shape (two ecologically important traits in sympatrically divergent Midas cichlids) and relate that to genetic variation in mitochondrial control region and microsatellites. Using these four datasets, we analyze variation between and within two Nicaraguan lakes: a crater lake where multiple Midas cichlids have been described and a lake where the source population lives. We do not observe any within‐lake clustering consistent across morphological traits and genetic markers, suggesting the absence of sympatric divergence in A. centrarchus . Genetic differentiation between lakes was low and morphological divergence absent. Such morphological similarity between lakes is found not only in average morphology, but also when analyzing covariation between traits and degree of morphospace occupation. A combined analysis of the mitochondrial control region in A. centrarchus and Midas cichlids suggests that a difference between lineages in the timing of crater lake colonization cannot be invoked as an explanation for the difference in their levels of diversification. In light of our results, A. centrarchus represents the ideal candidate to study the genomic differences between these two lineages that might explain why some lineages are more likely to speciate and diverge in sympatry than others. Abstract : We study the intraspecific morphological and genetic variation in Archocentrus centrarchus, a cichlid fish that inhabits the same lakes of sympatrically speciating Midas cichlid fish. We fail to find any signs of diversification in this fish. Our results suggest that this species is the ideal candidate to investigate which factors favor sympatric speciation in certain lineages.